1980
DOI: 10.1002/1097-0142(19800701)46:1<215::aid-cncr2820460136>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal involvement in non-Hodgkin's lymphoma

Abstract: A total of 813 patients admitted to Roswell Park Memorial Institute from 1963-1972 with non-Hodg-kin's lymphoma (NHL) were reviewed for gastrointestinal (GI) involvement. Primary involvement was found in 71 amid secondary involvement in 31 patients. Occult GI involvement was detected in 46% of the autopsy cases. The median survival time after the diagnosis of secondary GI involvement was nine months. The occuirrence of primary GI-NHL was: 33 in the stomach, 18 in the small intestine, 14 in the ileocecal area i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
156
0
12

Year Published

1985
1985
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 387 publications
(183 citation statements)
references
References 19 publications
15
156
0
12
Order By: Relevance
“…Those with tumours <10cm had a better survival than those with tumours > 10 cm (P < 0.05 - Figure 3). the past few years (Lim et al, 1977;Lewin et al, __ -1978;Hermann et al, 1980;Weingrand et al, 1982;Brooks & Enterline, 1983) By contrast our study comprises 29 patients r size <nOcm (II alive, 2 dead)s (a) tumour treated in a single institution. While we used Ocm (7 alive1 9 dead).…”
Section: Survivalsupporting
confidence: 92%
See 3 more Smart Citations
“…Those with tumours <10cm had a better survival than those with tumours > 10 cm (P < 0.05 - Figure 3). the past few years (Lim et al, 1977;Lewin et al, __ -1978;Hermann et al, 1980;Weingrand et al, 1982;Brooks & Enterline, 1983) By contrast our study comprises 29 patients r size <nOcm (II alive, 2 dead)s (a) tumour treated in a single institution. While we used Ocm (7 alive1 9 dead).…”
Section: Survivalsupporting
confidence: 92%
“…As far as the incidence of the various histological categories is concerned our findings are essentially similar to other series (Lim et al, 1977;Lewin et al, 1978;Hermann et al, 1980). Using Rappaport's Classification, we found that only one patient (3.5%) demonstrated a nodular architectural pattern.…”
Section: Survivalmentioning
confidence: 45%
See 2 more Smart Citations
“…These differences may have been associated with the difference in response to treatment and patient survival. A better prognosis for gastric lymphoma compared with other localizations has been described previously, 1,4,8,11,17,18,21,24,25 although several authors showed no difference in the prognosis between gastric lymphoma and intestinal lymphoma. 5,9,[13][14][15]19,20,22,23 Few publications have shown prognostic data on patients with both gastric and intestinal involvement.…”
Section: Discussionmentioning
confidence: 50%